Triple-shrine Temple to the northwest of Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The details of one of the shrines from the Triple-shrine Temple to the northwest of Mahanaleshwar Temple, are noteworthy. The base moudlings of the vedibandha are plain and bereft of any ornamentation. At the jangha (wall) level, the intermediate and corner projections have different designs. They also vary in size. Proportionately, the corner projection is one-third of the central wide projection, while the intermediate projections are half of the central projection.